2021
DOI: 10.1016/j.ijid.2020.10.068
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of urinary tract infections in hospitalized adults in Ghana: The role of the clinical microbiology laboratory in improving antimicrobial stewardship

Abstract: Background: The inappropriate use of antibiotics is a global threat. Clinical microbiology laboratory testing can support optimal antibiotic prescribing for many conditions. The purpose of this study was to characterize antibiotic usage in the context of treatment of uncomplicated urinary tract infection (UTI) received through a Ghanaian Accident & Emergency, which found high rates of improper usage. Methods: A prospective cohort study recruited patients >18 years of age who were admitted to a large Ghanaian t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Once implemented, the data from GLASS can be used for modifying standard treatment guidelines for empirical treatment of suspected UTI while awaiting culture AST results. Experience from countries such as Ghana and Thailand emphasize the use of clinical microbiology for setting up and improving antimicrobial stewardship [10,34]. Once an antimicrobial stewardship programme is set up, it needs to be fully supported and regularly evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once implemented, the data from GLASS can be used for modifying standard treatment guidelines for empirical treatment of suspected UTI while awaiting culture AST results. Experience from countries such as Ghana and Thailand emphasize the use of clinical microbiology for setting up and improving antimicrobial stewardship [10,34]. Once an antimicrobial stewardship programme is set up, it needs to be fully supported and regularly evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Other published studies from sub-Saharan Africa over the last 5 years have focused on small numbers of patients presenting with suspected UTIs that included students, pregnant women, vulnerable people such as those with diabetes or cancer, and children. Management of UTIs was poor and a call has been made from the West African country Ghana for more utilization of urine culture and antibiotic resistance profiles and more tailored use of antibiotics in response to culture results [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the same studies AMR rates as high as 95% have been reported to antibiotics used for treating UTIs [9][10][11] . Whilst there is limited information about the general national prevalence of UTIs in Ghana, two studies have reported 42.75% prevalence in pregnant women [13] and 86% among hospitalized adults [14]. The proportion of multi-drug resistant (MDR) UTIs have been reported to be as high as 93.6% in Ghana [10], [12].…”
Section: Of 14mentioning
confidence: 99%
“…In the same studies, AMR rates to antibiotics used for treating UTIs as high as 95% have been reported [ 9 , 10 , 11 ]. Whilst there is limited information about the general national prevalence of UTIs in Ghana, two studies have reported 42.75% prevalence in pregnant women [ 12 ] and 86% among hospitalized adults [ 13 ]. The proportion of multi-drug resistant (MDR) UTIs has been reported to be as high as 93.6% in Ghana [ 10 , 14 ].…”
Section: Introductionmentioning
confidence: 99%